Amelioration of the Protein Expression of Cox2, NFκB, and STAT-3 by Some Antioxidants in the Liver of Sodium Fluoride–Intoxicated Rats - Alhusaini, Ahlam (Dose Response, 2018)
The present study aimed to explore the efficiency of N-acetyl cysteine (NACC) or thymoquinone (TMQ) alone or in combination in the downregulation of inflammatory molecule expression and decreasing hepatic injury in response to sodium fluoride (SF). Sodium fluoride upregulated serum alanine and aspartate transferases activities, tumor necrosis factor α and hepatic malondialdehyde and nitric oxide levels, and the expression of cyclooxygenase 2, nuclear factor κB cell, and signal transducer and activator of transcription 3. In contrast, hepatic glutathione level, superoxide dismutase activity, and nuclear factor erythroid 2-related factor 2 expression were decreased. However, the concurrent treatment with antioxidants, alone or in combination, modulated the levels of these parameters. Histopathological examination revealed that SF treatment resulted in focal areas of massive hepatic degeneration and many degenerated hepatocytes, whereas the treatment with TMQ or NACC exhibited moderate improvement in cellular degeneration of the liver with many abnormal cells. Rats receiving a combination of TMQ and NACC showed marked improvement in cellular degeneration of liver with apparently normal hepatic architecture with very few degenerated hepatocytes. The results also revealed that the combination of TMQ and NACC is the most effective regimen in ameliorating SF toxicity, suggesting their efficacy against the toxicity of fluoride compounds. Their activities might be mediated via multiple molecular pathways.